Possibilidades de diálogo do design com o artesanato de linha de Tobias Barreto/SE - Santos, Anderson de Jesus (2022)
Embroidery is a practice, an artistic practice that developed as a technique especially focused on the universe of women, as an activity in the domestic environment, being a space that can be considered of social and economic invisibility, especially around the 18th century in Europe. bourgeois and industrial. Over the years, it is understood that the craft activity was replaced by the production of the industrial era (17th and 18th centuries), giving rise to the designer's craft to enhance the large-scale production and communication of products and services to increase consumption. In this way, the research analyzed the emergence of a field of Design focused on the spheres of popular culture, based on ethics and sustainability, being operationalized by collaborative methods based on the assumption that, in this way, the designer can contribute positively to the processes creators of craftsmanship. The methodology is based on the theoretical assumptions of qualitative exploratory research that include a bibliographic and documentary survey, a case study at the Community Association of Embroiders and Residents of Povoado Nova Brasília, in Tobias Barreto/SE. The research demonstrated that the interaction processes of Design in the Tobias Barreto’s handicraft can be placed in a horizontal and collaborative way. In this sense, the use of collaborative processes in the relationship between Design and craftsmanship proves to be effective in providing collective learning and exchange of knowledge among all the actors involved, in a balanced and respectful way, in order to establish new means of creative processes that can contribute to the technical and socioeconomic development of embroiderers.